2016
DOI: 10.1021/acs.chemmater.6b03013
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Supramolecular Polymer Binders for Lithium–Sulfur Batteries That Adapt Their Transport Properties in Operando

Abstract: π-Stacked perylene bisimide (PBI) molecules are implemented here as highly networked, redox-active supramolecular polymer binders in sulfur cathodes for lightweight and energy-dense Li-S batteries. We show that the in operando reduction and lithiation of these PBI binders sustainably reduces Li-S cell impedance relative to non-redox active conventional polymer binders. This lower impedance enables high-rate cycling in Li-S cells with excellent durability, a critical step toward unlocking the full potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…[79] Later on, other linear polymers including sulfonated poly(ether ether ketone), [80] poly(vinylidene difluoride-trifluoroethylene), [81] poly(3,4-ethyle nedioxythiophene):polystyrene sulfonate (PEDOT:PSS), [82] polyamide-6, chitosan sulfate ethylamide glycinamide, [83] benzimidazole-containing poly(arylene ether ketone), and sulfonated poly(arylene ether ketone-co-benzimidazole) [84] also have been reported to show good polysulfide anchoring ability. [87] Recently, Cui et al reported an aqueous inorganic polymer binder, ammonium polyphosphate (APP), which acquires not only polysulfide adsorption capability but also the flameretardant property (Figure 4D). Funct.…”
Section: Immobilization Of Polysulfidementioning
confidence: 99%
“…[79] Later on, other linear polymers including sulfonated poly(ether ether ketone), [80] poly(vinylidene difluoride-trifluoroethylene), [81] poly(3,4-ethyle nedioxythiophene):polystyrene sulfonate (PEDOT:PSS), [82] polyamide-6, chitosan sulfate ethylamide glycinamide, [83] benzimidazole-containing poly(arylene ether ketone), and sulfonated poly(arylene ether ketone-co-benzimidazole) [84] also have been reported to show good polysulfide anchoring ability. [87] Recently, Cui et al reported an aqueous inorganic polymer binder, ammonium polyphosphate (APP), which acquires not only polysulfide adsorption capability but also the flameretardant property (Figure 4D). Funct.…”
Section: Immobilization Of Polysulfidementioning
confidence: 99%
“…As shown in Figure , if the electrode active material itself has both electrical conductivity and suitable adhesion or other properties that help improve ion/electron conductivity and inhibit the polysulfide dissolution, the electrode performance could be greatly enhanced. On one hand, some polymer binders showed excellent properties in reducing Li–S cell impedance, actively regulating ion transport and enabling strongly anchoring polysulfides, and some conductive polymers have been used as binders in some inorganic electrodes . By selecting some special current collectors, some sulfur‐containing polymers such as rubber products and sulfur–limonene polysulfide can act as both active material and binder at the same time to form a binder‐free and conductive agent‐free electrode for use as the cathode of Li–S batteries.…”
Section: Potential Of Sulfur‐containing Polymer‐based Li–s Batteriesmentioning
confidence: 99%
“…Accordingly, there is significant current activity towards developing binder‐free electrode structures . However, there is also an increasing interest in identifying or developing new binder materials with properties that enable improved electrochemical performance through properties such as electronic conductivity or by interaction with polysulfides …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] However,t here is also an increasing interest in identifying or developing new binder materialsw ith properties that enable improved electrochemical performance through properties such as electronic conductivity or by interaction with polysulfides. [32][33][34][35][36][37][38][39][40] We previously reported on the benefits of using poly(ethylene oxide) (PEO) [41] or ac ombination of PEO with poly(vinyl-We report here aw ater-based functional binder framework for the lithium-sulfur battery systems, based on the general combination of ap olyether and an amide-containing polymer. These binders are appliedt op ositive electrodes optimised towards high-energye lectrochemical performance based only on commercially availablem aterials.E lectrodes with up to 4mAh cm À2 capacity and 97-98 %c oulombic efficiency are achievablei ne lectrodes with a6 5% total sulfur content and ap oly(ethylene oxide):poly(vinylpyrrolidone) (PEO:PVP) binder system.E xchange of either binder component foradifferent polymerw ith similarf unctionality preserves the high capacity and coulombic efficiency.T he improvement in coulombic effi-ciency from the inclusion of the coordinating amide group was also observed in electrodes where pyrrolidonem oieties were covalently grafted to the carbon black, indicating the role of this functionality in facilitating polysulfide adsorption to the electrode surface.T he mechanical properties of the electrodes appear not to significantly influence sulfur utilisation or coulombic efficiency in the short termb ut rather determine retention of these properties over extended cycling.…”
Section: Introductionmentioning
confidence: 99%